Internalisasi nilai harapan: Strategi integratif guru PAI dalam mengembangkan kultur sekolah berbasis karakter di Sekolah Dasar Negeri - Tjian, Melinda Khaila Nurfadilla; Supriadi, Udin; Komariah, Kokom Siti (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Character education in elementary schools often remains mere administrative jargon due to the gap between ideal school visions and actual classroom practices. This study aims to explore the internalization strategy of the "HARAPAN" school vision into Islamic Religious Education (PAI) learning to bridge this gap. Employing a qualitative case study design at a public elementary school in Bandung, this study collected data through in-depth interviews and participant observation, validated through source triangulation, and analyzed using Miles, Huberman, and Saldaña’s interactive model (data condensation, data display, and verification). The results demonstrate that value internalization was successfully achieved through a "Hybrid Approach" synergizing school rituals with creative teaching methods. While "Harmonious" and "Religious" values were deeply embedded through social engineering, this study reveals a critical failure in internalizing the "Amanah" (responsibility) value. A "moral knowing-doing gap" was observed, where students understood obligations but failed to execute them without supervision. This study concludes that macro-level school culture does not automatically shape micro-level independence without measurable behavioral conditioning. Abstrak Pendidikan karakter di sekolah dasar sering kali terjebak pada jargon administratif akibat kesenjangan antara visi ideal sekolah dan praktik nyata di kelas. Penelitian ini bertujuan mengeksplorasi strategi internalisasi visi sekolah "HARAPAN" (Harmonis, Aktif, Religius, Amanah, Peduli, Aman, Nyaman) ke dalam pembelajaran Pendidikan Agama Islam (PAI) guna menjembatani kesenjangan tersebut. Menggunakan desain studi kasus kualitatif di sebuah SDN di Bandung, data dikumpulkan melalui wawancara mendalam dan observasi partisipatif, divalidasi melalui triangulasi sumber, serta dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa internalisasi nilai berhasil dicapai melalui "Pendekatan Hibrida" yang menyinergikan ritual sekolah dengan metode kreatif guru. Nilai "Harmonis" dan "Religius" tertanam kuat melalui rekayasa sosial, namun ditemukan kegagalan kritis pada internalisasi nilai "Amanah" (tanggung jawab). Terjadi fenomena moral knowing-doing gap, di mana siswa memahami kewajiban namun gagal melaksanakannya tanpa pengawasan. Studi ini menyimpulkan bahwa budaya sekolah makro tidak serta-merta membentuk karakter mandiri tanpa adanya pengkondisian perilaku yang terukur.